Project-Based Learning with Interactive Video: Enhancing Language Learning Outcomes and Critical Thinking in Primary Education - Icuk Rahman; Weni Yulastri; Alfroki Martha (Journal of Education Research, 2026)
The quality of Indonesian language instruction in elementary schools is closely related to the instructional approaches and media teachers employ. This study examined the effects of Project-Based Learning (PjBL) integrated with interactive video on the Indonesian language learning outcomes of fifth-grade students. Using an ex post facto quantitative design, this research was conducted with fifth-grade students across public elementary schools in the Bukit Kerman District. Data were collected through documentation of student scores and a structured questionnaire, and analyzed using simple linear regression and multiple regression techniques. The results indicated that PjBL implementation had a significant independent effect on learning outcomes (β = 0.512; p < 0.001; R² = 0.262), as did interactive video utilization (β = 0.487; p < 0.001; R² = 0.237). When examined simultaneously, both variables together explained 40.3% of the variance in student achievement (R² = 0.403; F = 28.74; p < 0.001), suggesting that the integration of active, project-driven pedagogy with dynamic multimedia supports the development of higher-order language skills among young learners and offers a practically viable approach to improving Indonesian language instruction in rural elementary school settings.